(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Copper oxide thin films have been deposited on glass and stainless steel substrates by using a simple, safe and environmental friendly chemical solution method known as successive ionic layer adsorption reaction (SILAR). The films were prepared by successively dipping them for 20s each in a solution of 1 M NaOH and then in a solution of 0.1M copper complex. Temperature of the NaOH solution was 700C, while that of the copper complex solution with ( pH 8- 12) was maintained at room temperature. The films were characterized by X-ray diffraction (XRD), Energy dispersive X-ray analysis (EDAX) and scanning electron microscopy (SEM) The XRD measurements showed that formation of CuO nanostructures on glass substrates are more crystalline than that are on stainless steel substrates. SEM images reveals that the grain sizes of the CuO nanostructures deposited on stainless steel were larger than films deposited on glass substrate. Copper oxide films deposited using glass substrates showed a better morphology, higher crystallinity and better percentage ratio of the Cu/O composition than films deposited on stainless steel substrates.